The Development Process of Innovation of Accounting Cycle Simulation - Eka Wirajuang Daurrohmah (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2023)
Basic accounting learning is about the accounting cycle. One of the competency achievements of undergraduate accounting students is to be able to understand the accounting cycle and make financial reports. However, not a few accounting students who when they graduate from the course still do not understand the accounting cycle and make financial reports, especially with the open distance learning system. This paper aims to create learning innovations about the accounting cycle so that students easily understand the accounting cycle and can make financial reports. This learning innovation uses virtual reality and gamification technology. The methods used in this study is research and development study and ADDIE model used to the development model. The result of this study is the development of innovation of accounting cycle simulation can make more interesting and easier to understand about accounting cycle learning for student.